Presencia de Trypanosoma minasense (Kinetoplastida: Trypanosomatidae) en Alouatta palliata (Primates: Cebidae) de Costa Rica - Chinchilla Carmona, Misael (2005)
A Trypanosoma from the howler monkey Alouatta palliata was studied. Measures, as well as its biological characteristics (mice infection and failure to infect Triatominae) identify this parasite as Trypanosoma minasense. This organism is found for the first time in Costa Rica.